Pengaruh Model Pembelajaran Flipped Classroom terhadap Penguasaan Konsep dan Kepuasan Belajar Mahasiswa pada Mata Kuliah Etika dan Hukum Kebidanan - Siduppa, Basuki Rahmat Masdi; Darmiati, Darmiati (JURNAL KESEHATAN DELIMA PELAMONIA, 2024)
Mastery of midwifery ethics and legal concepts as well as student learning satisfaction are essential components in shaping professional competencies of midwives. However, conventional learning methods are often less effective in promoting active student engagement. The Flipped Classroom model is considered an innovative approach that combines online self-directed learning with interactive face-to-face activities. This study aimed to analyze the effect of the Flipped Classroom learning model on concept mastery and learning satisfaction among students in the Midwifery Ethics and Law course. This research employed a quasi-experimental design with pre-test and post-test control groups. The sample consisted of 60 fourth-semester students divided into an experimental group and a control group. Data were collected using a concept mastery test and a learning satisfaction questionnaire. Data analysis was performed using independent t-tests with a significance level of p<0.05. The results showed a significant increase in the mean concept mastery scores in the experimental group (from 61.2 to 84.6) compared to the control group (from 62.1 to 72.3) with p=0.000. The learning satisfaction score was also higher in the experimental group (mean 4.35) than in the control group (mean 3.68) with p=0.000. The Flipped Classroom learning model is effective in improving concept mastery and learning satisfaction among midwifery students.